Affinity, avidity and kinetics in immune recognition - van der Merwe, Anton (Henry Stewart Talks, 2020)
Challenges of immune recognition, Key binding concepts, Affinity, Kinetics, Avidity, Measuring binding properties, Cell surface molecules